Genomic characterization of large rearrangements of the LDLR gene in Czech patients with familial hypercholesterolemia - Goldmann, Radan; Tichý, Lukáš; Freiberger, Tomáš; Zapletalová, Petra; Letocha, Ondřej; Soška, Vladimír; Fajkus, Jiří; Fajkusová, Lenka (Bmc medical genetics, 2010)
BACKGROUND: Mutations in the LDLR gene are the most frequent cause of Familial hypercholesterolemia, an autosomal dominant disease characterised by elevated concentrations of LDL in blood plasma. In many populations, large genomic rearrangements account for approximately 10% of mutations in the LDLR gene. METHODS: DNA diagnostics of large genomic rearrangements was based on Multiple Ligation dependent Probe Amplification (MLPA). Subsequent analyses of deletion and duplication breakpoints were performed using long-range PCR, PCR, and DNA sequencing. RESULTS: In set of 1441 unrelated FH patients, large genomic rearrangements were found in 37 probands. Eight different types of rearrangements were detected, from them 6 types were novel, not described so far. In all rearrangements, we characterized their exact extent and breakpoint sequences. CONCLUSIONS: Sequence analysis of deletion and duplication breakpoints indicates that intrachromatid non-allelic homologous recombination (NAHR) between Alu elements is involved in 6 events, while a non-homologous end joining (NHEJ) is implicated in 2 rearrangements. Our study thus describes for the first time NHEJ as a mechanism involved in genomic rearrangements in the LDLR gene.
Keywords: Receptors, LDL; Czech Republic; lidé; Alu Elements; hyperlipoproteinemie typ II; Molecular Sequence Data; LDL-receptory; Hyperlipoproteinemia Type II; genová přestavba; Gene Rearrangement; Base Sequence; Humans; Česká republika; elementy Alu; molekulární sekvence - údaje; sekvence nukleotidů